Implementasi Tanggung Jawab Pengusaha Terhadap Pemeliharaan Kesehatan Bagi Pekerja Dengan Perjanjian Kerja Jangka Waktu Tertentu - Juli Rizkia, Andi Annisa; Asyhadie, Zaeni (Fakultas Hukum Universitas Mataram, 2024)
This research has the purpose to find out the employer's legal responsibility against health care insurance for workers with a certain period of time work agreement, and find out the factor that affects the employer's legal responsibility against health care insurance for workers with a certain period of time work agreement in PT. Cahaya Mustika Mutiara. This research is empirical legal research. The result of this study showed that the employer should provide health care services include health improvement, prevention healing, and health recovery. The factors affect the employer's legal responsibility against health care for the workers namely, legislation factors, cultural factors, and facilities factors.